REHABILITATION NARCOTICS ABUSERS IN PERSPECTIVE CRIMINAL POLICY - Maria Novita Apriyani (Surakarta Law and Society Journal, 2020)
Placing users and abusers of narcotics and psychotropics into rehabilitation institutions through judges’ decision is an alternative of proper criminal sanction in the law enforcement toward narcotics abusers and preventing narcotics illegal circulations. Compared with sending criminals into the jail, criminal sanctions through rehabilitation are done by giving medical and social rehabilitation. Based on the results of the discussion it can be said: First, An addict and or narcotics abusers and or victim of narcotic abuse cannot abort the criminal act of narcotics abuse that has been done athough the one is attending are has attended rehabilitation program (the article one hundred three) to Act Number 35 of 2009 about Narcotics. Second, Rehabilitation as a non penal mediation in criminal law policy doesnot have to be a phsyical punishment. A rehabilitation program that is attended by an addict and or victim of narcotics abuse doesnot stop that one from the criminal act that he has done. Third, A punishment given to an addict or victim of narcotics abuse is rehabilitation not phsyical punishment. Keyword: rehabilitation, narcotic abusers, criminal policy.